PEMANFAATAN MINYAK SERAI (CYMBOPOGON CITRATUS) MENJADI SABUN MANDI PADAT - Rahmi, Emilia; Hasbaini, Hasbaini; Hanifah, Rulia; Maulina, Dian; Mislina, Mislina (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2025)
Soap is one of the essential products in human life, used to cleanse the body from dust and dirt on the skin. Bath soap has developed into a primary necessity in society. Soap can also be used to treat skin diseases caused by bacteria and fungi. In South Aceh, there is an abundance of lemongrass plants (Cymbopogon Citratus), making them an easily accessible raw material for making solid soap. The processing of lemongrass oil soap involves turning it into soap using ingredients such as lemongrass oil, VCO (Virgin Coconut Oil), NaOH (sodium hydroxide), and water. All the ingredients are first weighed according to specified measurements, then mixed until thickened, poured into molds, and left to set for 2 days. The method used in the production of lemongrass oil soap is the experimental method. After the lemongrass soap is produced, its physical properties, such as shape, color, and texture, are observed. In the moisture content test, the water content found was 2.24% in sample 1, 2.99% in sample 2, and 3.59% in sample 3. In this case, the amount of lemongrass oil used affects the water content—the more lemongrass oil used, the higher the water content.